CONTINUOUS PROFESSIONAL DEVELOPMENT IN HEALTHCARE - Aristayudha, A A Ngurah Bagus; Richadinata, Kadek Riyan Putra; Rettobjaan, Vitalia Fina Carla (E-Jurnal Manajemen; Vol 10 No 2 (2021)DO - 10.24843/EJMUNUD.2021.v10.i02.p04, 2021)
Industry 4.0 has shown that digital is everywhere. The Healtcare industry is in the "long fuse, big bang" cluster meaning companies will face their disruption in three to five years and therefore have more time to change (Deloitte 2015). Which shows that in a few years there will be a transformation in the way the health care industry works. This study was conducted to determine the effect of continued professional development (CPD) in the health care industry. The sample in this study were 107 people where the results of data collection were processed using simple linear regression analysis techniques. The research results prove that continued professional development has a positive and significant effect on individuals in the health care industry and that continued professional development has a positive and significant effect on organizations in the health care industry. This shows that organizations / companies in the health care industry are expected to take responsibility for the development of employees' abilities and individuals / employees in the health care industry are expected to understand that CPD is an investment in career development. Keywords : continued professional development, motivation, perception, benefits